A distributed energy equipment with highly efficient heat dissipation. Issue 5 (April 2021) - Wang, Zhongyu; Liu, Peichen; Jiang, Qiushuo; Wan, Yi; Yang, Chengcheng; Wang, Xu; Liang, Jiachen
Abstract: Distributed energy technology is an important development direction of the world energy technology in the future [1]. It has the characteristics of high energy utilization efficiency, small negative impact on the environment, improving the reliability of energy supply and good economic benefits. At present, China's distributed energy technology is not mature enough. Aiming at the heat dissipation problem of distributed energy technology, we propose a method of using natural rainwater air cooling to realize the efficient heat dissipation of distributed energy equipment. It provides a reference for the development of distributed energy technology.